X-exome sequencing identifies a HDAC8 variant in a large pedigree with X-linked intellectual disability, truncal obesity, gynaecomastia, hypogonadism and unusual face. Issue 8 (12th August 2012) - Harakalova, Magdalena; van den Boogaard, Marie-Jose; Sinke, Richard; van Lieshout, Stef; van Tuil, Marc C; Duran, Karen; Renkens, Ivo; Terhal, Paulien A; de Kovel, Carolien; Nijman, Ies J; van Haelst, Mieke; Knoers, Nine V A M; et al.
Abstract : Background: We present a large Dutch family with seven males affected by a novel syndrome of X-linked intellectual disability, hypogonadism, gynaecomastia, truncal obesity, short stature and recognisable craniofacial manifestations resembling but not identical to Wilson-Turner syndrome. Seven female relatives show a much milder expression of the phenotype. Methods and results: We performed X chromosome exome (X-exome) sequencing in five individuals from this family and identified a novel intronic variant in the histone deacetylase 8 gene ( HDAC8 ), c.164+5G>A, which disturbs the normal splicing of exon 2 resulting in exon skipping, and introduces a premature stop at the beginning of the histone deacetylase catalytic domain. The identified variant completely segregates in this family and was absent in 96 Dutch controls and available databases. Affected female carriers showed a notably skewed X-inactivation pattern in lymphocytes in which the mutated X-chromosome was completely inactivated. Conclusions: HDAC8 is a member of the protein family of histone deacetylases that play a major role in epigenetic gene silencing during development . HDAC8 specifically controls the patterning of the skull with the mouse HDAC8 knock-out showing craniofacial deformities of the skull. The present family provides the first evidence for involvement of HDAC8 in a syndromic form of intellectual disability.